EFFICIENCY OF THE FUNCTIONING OF TWO STOCK EXCHANGES IN KAZAKHSTAN AND ISSUES RELATED TO THEIR SUBSEQUENT MERGER - Shayakhmetov, Arman; Kosbayeva, Aigerim; Abuova, Aknar (Nazarbayev University Graduate School of Public Policy, 2024)
The stock exchange is a fundamental part of the country's financial market, which, in turn, contributes to economic stability and growth. The effective functioning of stock exchanges is a crucial component of the modern financial system, which has a significant impact on the economic development of the country. Nowadays, the role of stock exchanges is in informing the investment environment and providing financial stability, which is becoming more important in the worldwide economic changes. In the context of Kazakhstan, there are two stock exchanges, namely, the KASE, operating under Kazakhstani law and the AIX, which exists within the jurisdiction of AIFC. Despite the fact that AIX and KASE are established in the form of private commercial entities, both stock exchanges are ultimately owned by the state body - the National Bank of the RK. Consequently, mentioned stock exchanges are subject to state regulation. The purpose of this research is to investigate some aspects of AIX and KASE related to their performance affecting the attractiveness of the RK’s financial market. Also, research strives to identify options for potential merger of stock exchanges in Kazakhstan. This research contains an introduction covering background facts, and establishing a basis for future research. There are major parts of the literature review explaining past international experience for the merger of stock exchanges, whose findings discover findings that can be applied to Kazakhstan’s experience and gaps that potentially can become a problem within and after the merger procedure. This research proposal also applies research methods by means of which data for the analysis shall be collected. Conclusion part provides recommendations for future actions to be performed in order to ensure smooth integration of merger in order to secure market participants from shocks and uncertainties.
Keywords: Type of access: Open access; AIX; KASE; Merger; Stock exchanges